Organizational aspects of irrigation management in Kalankuttiya block, Mahaweli system H, Sri Lanka during the 1986 dry season - Moragoda, R.; Groenfeldt, D. (International Irrigation Management Institute, 1989)
Field research on water flows and agricultural production in the Kalankuttiya Block of Mahaweli System H was initiated by IIMI staff in mid-1985 during Yala (dry season). The primary focus was to understand the effects of irrigation management practices on crop diversification from rice to "other food crops" (OFCs) such as chili, lentil, soybean, and onion. Faced with immanent self-sufficiency in rice production, but continuing large-scale imports of non-rice food crops, the government is trying to promote the cultivation of OFCs, which require intermittent irrigation, in schemes designed primarily for rice cultivation and more or less continuous water flows.